EFFORT TO INCREASE CATTLE FARMERS CAPACITY IN APPLICATION OF COMPACT ORGANIC FERTILIZER TECHNOLOGY (CASE STUDY ON FARMER GROUP LEMBAH PAMULI NORTH MINAHASA REGENCY) - Endoh, Eusebius; Wantasen, Erwin (International Journal of Research -GRANTHAALAYAH, 2017)
The aim of the study was to know cattle farmers ability and their characteristics to implement technology of compact organic fertilizer made from cattle manure. The program was conducted in farmers group namely Lembah Pamuli located in Wori sub district regency of North Minahasa. The objects of activity consisted of 15 of cattle farmers whereas the materials included cattle’s manure, ureum, probiotic EM4 and other materials that can supported the processing of organic fertilizer production. The approach to the group was extension and training. The result of this program showed that 66.67% of the participant in extension and training was men and they were 43 years old in averages. Thirty percent of their level of education was elementary school, 40% in secondary school, 22% senior high school and 8% at level of diploma. According to pre and posttest toward members group of Lembah Pamuli in line with their capacity to produce organic fertilizer showed that averages score increase by 47.94% after they followed the extension and training to produce organic fertilizer. The breeder’ knowledge was significantly different (P<0.01) before and after learning of how to produce organic fertilizer from cattle manure.